Construcción y validación de la “Escala de problemas sociales en población chilena” - Faúndez Abarca, Ximena Ligia (2022)
This article describes the construction and validation of the “Scale of Social Problems in Chile”. The scale was developed considering the main social issues at a national and municipal level. The instrument was validated using quantitative methodology, with a non-experimental cross-sectional design. The participants were 456 residents of the Valparaíso municipality, Chile. Cases were selected using quota sampling to reflect the demographic composition of the region in terms of the sex and age groups found in the municipality. Exploratory factor analysis was conducted using the Statistical Package for Social Sciences (SPSS) V24.0, while confirmatory factor analysis was performed with R console and the Rcmdr interface. These analyses made it possible to establish that the factor structure of the scale differentiates national problems from local ones.